Brazilians professionals repatriation: a policy analysis performed by Brazilian companies - Salgado, Thaís Ettinger; Oliva, Eduardo Camargo; Kubo, Edson Keyso de Miranda; Soares, Darticleia Almeida Sampaio da Rocha; Zambanini, Marcos Eduardo (Revista de Administração da UFSM, 2018)
With the objective of analyzing the policies in the repatriation programs practiced in Brazilian transnational companies, this research focused on studying the international management of Human Resources, as well as on deepening the policies and practices of Brazilian companies that have repatriation programs. For this, a descriptive research was carried out with a population limited to the Brazilian Transnational Rankings (2011 and 2012) conducted by Fundação Dom Cabral. Of the 52 companies listed, 25 participated in the survey, which took the form of an on-site interview. The information obtained was analyzed with the aid of the qualitative analysis software Atlas TI, showing that there is some kind of care by companies in reducing the uncertainties of the returnee, either through efficient communication and clarity about the possibilities of growth; attractive salaries and benefits; of support; or a specific contract guaranteeing return for both parties.